En jämförelse mellan kampsportstester och Wingate test: En tvärsnittsstudie på elitaktiva inom Judo och Taekwon-Do - Willmann, H.; Hytönen, L. (Operations Research and Financial Engineering, 2000-2023, 2023)
Purpose/aim The purpose of this study was to investigate whether there was any correlation between the Wingate anaerobic test performed on an ergometer cycle, the Wingate anaerobic test performed on an arm cycle and the sport specific tests: the Special Judo Fitness Test (SJFT) and the Multiple Frequency Speed of Kick Test (FSKT) on elite level athletes. Method The number of subjects was 12, of which 8 were men and 4 were women. 6 subjects were recruited from judo and 6 subjects from Taekwon-Do ITF. The selection criterias were that the subjects were on an elite level and would be around 17-35 years old. Elite level was defined as actively competing within the national team in the last three years or competing at international level in the last three years in terms of competition results, alternatively achieving the national team's selection criteria in the last three years. Additional requirements were to have a black belt in their respective sport and to have actively trained for at least 5 years. Results Looking at the results, strong correlations were noted between the Wingate anaerobic test and FSKT. This applied to FSKTtot and average power in lower body Wingate (R = 0.76; p = 0.077). However, the significance levels for the correlations were not met, which meant that the null hypothesis could not be rejected, and it could not be determined whether the correlations were due to randomness or not. Conclusion Strong correlations between Wingate and FSKT could be noted, especially between FSKTtot and "average power" in lower body Wingate. However, due to low significance levels, the null hypothesis could not be rejected. To ensure this trend and correlation, further studies are necessary with more participants (>12). A practical piece of advice for athletes and coaches is to try including lower body Wingate in the training program, to create variety in training.